PHOTOMETRIC RESEARCHES IN THE SELECTED KAPTEIN AREAS - Yasinskaya, M. P.; Tomak, L. Ph.; Zavershneva, L. A.; Dragunova, A. V. (Одеські астрономічні публікації, 2017)
B and V magnitudes of 4437 stars from Kaptein Areas No 64, 65, 86, 87, 88, 98 are obtained. The catalogue and the star maps are given.